Super-hydrophobic anti-icing coating based on fluorinated silicone rubber and preparation method of super-hydrophobic anti-icing coating

By using fluorosilicone rubber and organic and inorganic hybridization technology in superhydrophobic anti-icing coatings, the problem of degradation of anti-icing performance of existing coatings in low temperature environments is solved, and the efficient hydrophobicity of the coatings is achieved and the simplified process is achieved, which extends the icing time and reduces costs.

CN119662124APending Publication Date: 2025-03-21BEIJING GUODIAN FUTONG SCI & TECH DEV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411711023.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing superhydrophobic anti-ice coatings have reduced anti-ice performance in low temperature environments, and the coating process is complex, energy consumption is high and cost is high.

Method used

The superhydrophobic anti-ice coating based on fluorosilic rubber is used to organically combine the hydrophobic modified filler with the polymer matrix through organic and inorganic hybridization technology to simplify the coating process and use a single component to form a hydrophobic surface.

Benefits of technology

It improves the hydrophobicity and oleophobicity of the paint, extends the icing time, reduces the adhesion of ice and snow, and simplifies the process and reduces the cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662124A_ABST
    Figure CN119662124A_ABST
Patent Text Reader

Abstract

The invention discloses a super-hydrophobic anti-icing coating based on fluorinated silicone rubber and a preparation method of the super-hydrophobic anti-icing coating. The super-hydrophobic anti-icing coating comprises a colloidal material, a nanoparticle solvent, a curing agent and a catalyst in a mass ratio of (116-169): (116-152): (5-15): (2-4), the colloid material comprises nanoparticles A, fluorosilicone oil, silicone oil, a solvent A and an auxiliary agent A in a mass ratio of (22-33): (40-50): (10-20): (40-60): (4-6); and the nano split solvent comprises nano particles B, an auxiliary agent B and a composite solvent in a mass ratio of (12-24): (4-8): (100-120). Through an organic-inorganic hybridization technology, hydrophobic and modified filler parts in the raw materials are organically combined with a polymer matrix, the hydrophobic performance is optimized, and a hydrophobic surface is formed by a single component; through the processes of dispersing by combining an auxiliary agent with a solvent and the like, effective dispersion and combination of nano particles and a matrix are realized, and the combination effect of the coating nano filler and the matrix is improved; the adhesive force of the coating is 0 grade, the impact resistance is 45-50 kg.cm, the contact angle is larger than 150 degrees, the tangential ice adhesion strength is lower than 50 kPa, and the icing time is effectively prolonged to be larger than 80 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anti-icing coating, and in particular to a super-hydrophobic anti-icing coating based on fluorosilicone rubber and a preparation method thereof. Background Art

[0002] Power safety is the foundation of energy security. Disasters caused by changing climates and environments will threaten power safety, and icing disasters are particularly serious. Icing of transmission lines has a huge impact on people's lives, life, property safety, and the development of the national economy. In particular, for transmission lines with long transmission lines, large regional spans, and high voltage levels, in autumn and winter, when the transmission lines pass through low temperature and high humidity environments, icing disasters are prone to occur on the wires, causing problems such as line disconnection and tower collapse, leading to large-scale power outages and even collapse, threatening the safe and stable operation of the power grid. In addition, with the rise of the new energy industry, the scope of wind power development is expanding. Regions with abundant wind power resources are often accompanied by cold, humid, and icing-prone climates. The icing of wind turbine blades is increasingly restricting the development of wind power. At present, the mainstream protection technologies are mainly active deicing and anti-icing. Active deicing includes mechanical means of breaking ice and electric ice melting, which have problems such as poor timeliness and harsh construction environment. Anti-icing mainly relies on anti-icing materials, such as super-hydrophobic materials, photothermal materials, low surface energy materials, etc., which are applied on the surface of power equipment to reduce the amount of ice and delay ice formation. The advantages are that it can be pre-treated before the ice comes and the construction method is simple. It has been the focus of major research institutes in recent years. However, despite this, research in this area is still relatively basic. Before it can completely solve the problem of outdoor equipment icing, there are still many problems to be overcome, such as the poor compatibility of nanofillers and polymer matrices, which leads to material surface durability problems and greatly reduces the anti-icing performance of the coating in low temperature environments. Traditional super-hydrophobic anti-icing coatings are all in the form of primer and topcoat layered and sprayed multiple times, which is technically complex, energy-intensive, and costly. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to simplify the coating process of anti-icing coating while improving the anti-icing efficiency, and to provide a super-hydrophobic anti-icing coating based on fluorosilicone rubber; another purpose of the present invention is to provide a method for preparing the coating.

[0004] Technical solution: The super-hydrophobic anti-icing coating based on fluorosilicone rubber described in the present invention includes a colloidal material, a nanoparticle solvent, a curing agent and a catalyst, and the mass ratio thereof is 116-169:116-152:5-15:2-4; the colloidal material includes nanoparticles A, fluorosilicone oil, silicone oil, solvent A and auxiliary agent A, and the mass ratio thereof is 22-33:40-50:10-20:40-60:4-6; the nano-split solvent includes nanoparticles B, auxiliary agent B and a composite solvent, and the mass ratio thereof is 12-24:4-8:100-120; the nanoparticles A are one or more of nano-silicon dioxide, nano-aluminum hydroxide and nano-titanium dioxide; the nanoparticles B are one or more of gas-phase nano-silicon dioxide and nano-titanium dioxide.

[0005] Furthermore, the nanoparticles A are hydrophobically modified using hexamethylsilazane, perfluorodecyltrimethoxysiloxane or polydimethylsiloxane.

[0006] Furthermore, the fluorosilicone oil is a hydroxyl fluorosilicone oil with a molecular weight of 67,500 to 82,500 and a viscosity maintained at about 20,000, a hydroxyl fluorosilicone oil with a molecular weight of 58,500 to 71,500 and a viscosity maintained at about 15,000, a hydroxyl fluorosilicone oil with a molecular weight of 45,000 to 55,000 and a viscosity maintained at about 5,000, or one or more thereof; the silicone oil is a hydroxyl silicone oil with a molecular weight of 36,000 to 44,000 and a viscosity maintained at about 3,000, a hydroxyl silicone oil with a molecular weight of 22,500 to 27,500 and a viscosity maintained at about 1,000, a hydroxyl silicone oil with a molecular weight of 18,000 to 22,000 and a viscosity maintained at 800, or one or more thereof. The molecular weight determines the viscosity. Choosing hydroxy fluorosilicone oil with appropriate molecular weight can keep its viscosity within a reasonable range and ratio. Fluorosilicone oil has a large molecular weight and a higher viscosity than silicone oil, which can enhance the impact resistance of the polymer matrix. Copolymerization with silicone oil with small molecular weight and low viscosity can adjust the viscosity of the polymer matrix, thereby making it better mixed and dissolved with modified nanoparticle fillers to improve coating performance.

[0007] Furthermore, the solvent A is one or more of ethyl acetate, butyl acetate and cyclohexanone.

[0008] Furthermore, the auxiliary agent A is one or more of tetramethylsilane, KH-550 coupling agent, KH-560 coupling agent, and BYK-012 defoaming agent.

[0009] Furthermore, the nanoparticles B are hydrophobically modified by using one or more of polydimethylsiloxane, polydimethyldichlorosilane, and hexamethylsilazane. The nanoparticles in the gas phase have better dispersion performance, are more evenly mixed with the colloidal material, and have better organic-inorganic hybrid performance.

[0010] Furthermore, the auxiliary agent B is one or more of hexamethylsiloxane, perfluorooctyl triethoxysiloxane, and KH-570 coupling agent.

[0011] Furthermore, the composite solvent is one or more of ethanol, isopropanol, propanol, and tetrahydrofuran.

[0012] Furthermore, the curing agent is one or more of methyltributylacetonato silane, vinyltributylacetonato silane, and methyltriacetone silane; and the catalyst is one or more of dibutyltin dilaurate and stannous octoate.

[0013] The present invention also provides a method for preparing the coating, comprising the following steps:

[0014] Step (1): Nanoparticles A are dispersed in a mixture of deionized water and ethanol for hydrophobic modification;

[0015] Step (2): dispersing and drying to obtain modified nanoparticles A, preliminarily mixing with fluorosilicone oil and silicone oil, kneading in a vacuum kneader, dispersing, and grinding to obtain a base rubber;

[0016] Step (3): mixing, dispersing and stirring the base glue, solvent A and additive A to obtain a colloidal material;

[0017] Step (4): dispersing the nanoparticles B by mixing deionized water and ethanol for hydrophobic modification;

[0018] Step (5): dispersing and drying to obtain modified nanoparticles B, and uniformly dispersing the modified nanoparticles B with the auxiliary agent B and the composite solvent to obtain a nanoparticle solvent;

[0019] Step (6): Dispersing the colloidal material, nanoparticle solvent, curing agent, and catalyst, and evacuating the mixture to obtain a finished coating.

[0020] The modified nanoparticles A are first mixed with the polymer matrix, and the modified nanoparticles B are further mixed with the polymer matrix, which can increase the modified particle filler combined with the surface of the polymer matrix and improve the hydrophobicity and oleophobicity of the coating.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. Through the organic-inorganic hybrid technology, the hydrophobic and modified filler parts in the raw materials are organically combined with the polymer matrix, and the modified functional molecules are combined on the surface of the polymer material in a dispersed form to optimize the hydrophobic performance. Different from the primer and topcoat forms of the previous process, a hydrophobic surface can be formed by a single component; 2. Through process optimization, additives combined with solvent dispersion and other process operations, the effective dispersion and combination of nanoparticles and the matrix that provides strength are achieved, and the disadvantage of poor combination of the coating nanofiller and the polymer matrix is ​​improved; 3. The adhesion of the coating is level 0, the impact resistance is 45 to 50 kg·cm, the contact angle is greater than 150°, and the tangential ice adhesion strength is less than 50 kPa, so that ice and snow are not easy to adhere to the coating surface, and the icing time is effectively extended to more than 80 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a flow chart of the preparation process of the coating. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below in conjunction with the accompanying drawings. All reagents used are commercially available reagents.

[0024] Example 1

[0025] A super hydrophobic anti-icing coating based on fluorosilicone rubber is composed of a colloidal material, a nanoparticle solvent, a curing agent and a catalyst.

[0026] (1) Colloidal materials include:

[0027] Nanoparticle A: 8g nano-silicon dioxide, 8g nano-aluminum hydroxide and 4g nano-titanium dioxide

[0028] Fluorosilicone oil: 25g of hydroxyfluorosilicone oil with a molecular weight of 75,000 and a viscosity of 20,000, 10g of hydroxyfluorosilicone oil with a molecular weight of 65,000 and a viscosity of 15,000, and 5g of hydroxyfluorosilicone oil with a molecular weight of 50,000 and a viscosity of 5,000

[0029] Silicone oil: 5g of hydroxy silicone oil with a molecular weight of 40,000 and a viscosity of 3,000, 3g of hydroxy silicone oil with a molecular weight of 25,000 and a viscosity of 1,000, and 2g of hydroxy silicone oil with a molecular weight of 20,000 and a viscosity of 800

[0030] Solvent A: 30 g ethyl acetate, 5 g butyl acetate and 5 g cyclohexanone

[0031] Additive A: 1g tetramethylsilane, 1g KH-550 coupling agent, 1g KH-560 coupling agent and 1g BYK-012 defoamer

[0032] (2) Nano-fragmented solvents include:

[0033] Nanoparticle B: 6g of fumed nano-silicon dioxide and 4g of nano-titanium dioxide

[0034] Additive B: 1g hexamethylsiloxane, 2g perfluorooctyl triethoxysiloxane and 1g KH-570 coupling agent

[0035] Composite solvent: 30g ethanol, 20g isopropanol, 10g propanol and 40g tetrahydrofuran

[0036] (3) Curing agent: 3 g of methyl tributylacetonate oxime silane, 1 g of vinyl tributylacetonate oxime silane and 1 g of methyl triacetone oxime silane

[0037] (4) Catalyst: 1.5 g dibutyltin dilaurate and 0.5 g stannous octoate

[0038] The above-mentioned method for preparing the super-hydrophobic anti-icing coating based on fluorosilicone rubber comprises the following steps:

[0039] Step (1): Nanoparticles A are dispersed with a mixed dispersion solvent A of 10 g of deionized water and 40 g of ethanol, and hydrophobically modified with a modification aid A: 0.5 g of hexamethylsilazane, 0.5 g of perfluorodecyl trimethoxysiloxane and 1 g of polydimethylsiloxane;

[0040] Step (2): dispersing and drying to obtain modified nanoparticles A, placing them in an open mill with fluorosilicone oil and silicone oil for initial mixing for 5 hours, kneading in a vacuum kneader for 40 minutes, dispersing, and grinding them in a three-roll mill for 30 minutes to obtain a base rubber;

[0041] Step (3): the base rubber, solvent A and additive A are mixed and dispersed and stirred for 60 minutes at a speed of 600 r / min to obtain a colloidal material;

[0042] Step (4): the nanoparticles B are dispersed with a mixed dispersion solvent B of 6 g of deionized water and 24 g of ethanol, and hydrophobically modified with a modification aid B: 0.5 g of polydimethylsiloxane, 0.5 g of polydimethyldichlorosilane and 1 g of hexamethylsilazane;

[0043] Step (5): dispersing and drying the modified nanoparticles B at a speed of 600 r / min in a disperser, and uniformly dispersing the modified nanoparticles B with the auxiliary agent B and the composite solvent at a speed of 400 r / min to obtain a nanoparticle solvent;

[0044] Step (6): Disperse the colloidal material, nanoparticle solvent, curing agent and catalyst at a speed of 400 r / min, and evacuate for 20 minutes to obtain a finished coating.

[0045] Example 2

[0046] A super hydrophobic anti-icing coating based on fluorosilicone rubber is composed of a colloidal material, a nanoparticle solvent, a curing agent and a catalyst.

[0047] (1) Colloidal materials include:

[0048] Nanoparticle A: 12g of nano-silicon dioxide, 10g of nano-aluminum hydroxide and 8g of nano-titanium dioxide

[0049] Fluorosilicone oil: 30g of hydroxyfluorosilicone oil with a molecular weight of 75,000 and a viscosity of 20,000, 15g of hydroxyfluorosilicone oil with a molecular weight of 65,000 and a viscosity of 15,000, and 5g of hydroxyfluorosilicone oil with a molecular weight of 50,000 and a viscosity of 5,000

[0050] Silicone oil: 10g of hydroxy silicone oil with a molecular weight of 40,000 and a viscosity of 3,000, 6g of hydroxy silicone oil with a molecular weight of 25,000 and a viscosity of 1,000, and 4g of hydroxy silicone oil with a molecular weight of 20,000 and a viscosity of 800

[0051] Solvent A: 40 g ethyl acetate, 10 g butyl acetate and 10 g cyclohexanone

[0052] Additive A: 2g tetramethylsilane, 1g KH-550 coupling agent, 2g KH-560 coupling agent and 1g BYK-012 defoamer

[0053] (2) Nano-fragmented solvents include:

[0054] Nanoparticle B: 12g of fumed nano-silicon dioxide and 8g of nano-titanium dioxide

[0055] Additive B: 2g hexamethylsiloxane, 3g perfluorooctyl triethoxysiloxane and 3g KH-570 coupling agent

[0056] Composite solvent: 40g ethanol, 30g isopropanol, 10g propanol and 40g tetrahydrofuran

[0057] (3) Curing agent: 8 g methyl tributylacetonate oxime silane, 3 g vinyl tributylacetonate oxime silane and 4 g methyl triacetone oxime silane

[0058] (4) Catalyst: 2 g dibutyltin dilaurate and 2 g stannous octoate

[0059] The preparation method is different from that of Example 1:

[0060] Step (1): Nanoparticles A are dispersed with a mixed dispersion solvent A of 20 g of deionized water and 50 g of ethanol, and hydrophobically modified with a modification aid A: 1 g of hexamethylsilazane, 1 g of perfluorodecyl trimethoxysiloxane and 1 g of polydimethylsiloxane;

[0061] Step (4): The nanoparticles B are dispersed with a mixed dispersion solvent B of 10 g of deionized water and 30 g of ethanol, and hydrophobically modified with a modification aid B: 1 g of polydimethylsiloxane, 1 g of polydimethyldichlorosilane and 2 g of hexamethylsilazane.

[0062] Example 3

[0063] A super hydrophobic anti-icing coating based on fluorosilicone rubber is composed of a colloidal material, a nanoparticle solvent, a curing agent and a catalyst.

[0064] (1) Colloidal materials include:

[0065] Nanoparticle A: 8g nano-silicon dioxide, 8g nano-aluminum hydroxide and 4g nano-titanium dioxide

[0066] Fluorosilicone oil: 30g of hydroxyfluorosilicone oil with a molecular weight of 75,000 and a viscosity of 20,000, 15g of hydroxyfluorosilicone oil with a molecular weight of 65,000 and a viscosity of 15,000, and 5g of hydroxyfluorosilicone oil with a molecular weight of 50,000 and a viscosity of 5,000

[0067] Silicone oil: 8g of hydroxy silicone oil with a molecular weight of 40,000 and a viscosity of 3,000, 3g of hydroxy silicone oil with a molecular weight of 25,000 and a viscosity of 1,000, and 4g of hydroxy silicone oil with a molecular weight of 20,000 and a viscosity of 800

[0068] Solvent A: 40 g ethyl acetate, 10 g butyl acetate and 10 g cyclohexanone

[0069] Additive A: 1g tetramethylsilane, 1g KH-550 coupling agent, 1g KH-560 coupling agent and 1g BYK-012 defoamer

[0070] (2) Nano-fragmented solvents include:

[0071] Nanoparticle B: 6g of fumed nano-silicon dioxide and 4g of nano-titanium dioxide

[0072] Auxiliary agent B: 2g hexamethylsiloxane, 2g perfluorooctyl triethoxysiloxane and 2g KH-570 coupling agent

[0073] Composite solvent: 30g ethanol, 20g isopropanol, 10g propanol and 40g tetrahydrofuran

[0074] (3) Curing agent: 6 g of methyl tributylacetonate oxime silane, 1 g of vinyl tributylacetonate oxime silane and 1 g of methyl triacetone oxime silane

[0075] (4) Catalyst: 2 g dibutyltin dilaurate and 1 g stannous octoate

[0076] The preparation method is different from that of Example 1:

[0077] Step (1): Nanoparticles A are dispersed with a mixed dispersion solvent A of 10 g of deionized water and 50 g of ethanol, and hydrophobically modified with a modification aid A: 0.5 g of hexamethylsilazane, 0.5 g of perfluorodecyl trimethoxysiloxane and 1 g of polydimethylsiloxane;

[0078] Step (4): The nanoparticles B are dispersed in a dispersion solvent B using 6 g of deionized water and 24 g of ethanol, and hydrophobically modified using a modification aid B: 1 g of polydimethylsiloxane, 1 g of polydimethyldichlorosilane and 1 g of hexamethylsilazane.

[0079] Comparative Example 1

[0080] The difference from Example 1 is: Fluorosilicone oil: 30 g of hydroxyfluorosilicone oil with a molecular weight of 75,000 and a viscosity of 20,000, 15 g of hydroxyfluorosilicone oil with a molecular weight of 65,000 and a viscosity of 15,000, and 5 g of hydroxyfluorosilicone oil with a molecular weight of 50,000 and a viscosity of 5,000, without adding silicone oil components.

[0081] Comparative Example 2

[0082] The difference from Example 1 is: Silicone oil: 6 g of hydroxy silicone oil with a molecular weight of 40,000 and a viscosity of 3,000, 6 g of hydroxy silicone oil with a molecular weight of 25,000 and a viscosity of 1,000, and 4 g of hydroxy silicone oil with a molecular weight of 20,000 and a viscosity of 800, without adding fluorosilicone oil.

[0083] Comparative Example 3

[0084] The difference from Example 1 is that in step (1), the nanoparticles A are not hydrophobically modified.

[0085] Comparative Example 4

[0086] The difference from Example 1 is that no auxiliary agent A is added to the colloidal material.

[0087] Comparative Example 5

[0088] The difference from Example 1 is that in step (4), the nanoparticles B are not hydrophobically modified.

[0089] The coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to performance tests, and a simulated icing experiment (simulated icing conditions: ambient temperature -6°C, humidity>90%, precipitation intensity 4mm / h, wind speed: 5m / s) was conducted to test the delayed icing time, see Table 1 for details.

[0090]

[0091] Compared with Examples 1 to 3, the coatings have adhesion of level 0, impact resistance of 45 to 50 kg·cm, contact angle greater than 150°, and tangential ice adhesion strength less than 50 kPa, which makes it difficult for ice and snow to adhere to the coating surface, and can effectively extend the freezing time by more than 80 minutes. In comparison, the coating prepared in Example 3 has the best comprehensive performance. Silicone oil is a chain polymer with good weather resistance and hydrophobicity, small viscosity-temperature coefficient, and good compression resistance, but its surface tension is small; while the side groups of fluorosilicone oil are replaced by fluorine-containing groups, its weather resistance, high and low temperature resistance, stability and waterproof and oil-proof properties are better, and it has good compatibility with other additives. Fluorosilicone oil has good compatibility with the modifier nanoparticles. The nanoparticles provide them with active groups, which promote the copolymerization and cross-linking of fluorosilicone oil and silicone oil, making the two complementary in performance, improving the hydrophobicity and oleophobicity of the coating, and reducing the adhesion of ice and snow on the surface of the coating to level 0; after copolymerization, the impact resistance of the coating is improved; after fluorosilicone oil is dissolved in the nanoparticles and then copolymerized with silicone oil, the specific surface tension of the coating is improved, the contact angle is increased, the tangential ice adhesion strength is reduced, and the adhesion of ice and snow on the coating is further reduced.

[0092] Comparing Example 1 with Comparative Examples 1-2, the coating using silicone oil or fluorosilicone oil alone is inferior to the embodiment in terms of hydrophobicity, adhesion and anti-icing performance. When fluorosilicone oil or silicone oil is used alone, the small surface tension of silicone oil and the incompatibility of fluorosilicone oil with polar solvents or corrosive fluids result in poor overall performance of the coating; the compatibility with the modified nanoparticles deteriorates, and the modified nanoparticles cannot effectively improve the hydrophobicity and oleophobicity of the coating, and thus cannot effectively prevent ice and snow from adhering to the coating surface.

[0093] Comparing Example 1 with Comparative Examples 3 to 5, the properties of Comparative Examples 3 to 5, which did not add the modifying additive during the mixing of the components in the coating preparation process, were greatly reduced. This is mainly because the effective addition of additives combined with solvents during the mixing process can effectively disperse the nanoparticles and combine with silicone oil and fluorosilicone oil, improve the combination of nanofillers and polymer matrix through organic-inorganic hybridization, and optimize the hydrophobic properties of the material surface.

Claims

1. A super-hydrophobic anti-icing coating based on fluorosilicone rubber, characterized in that: The invention comprises colloidal material, nanoparticle solvent, curing agent and catalyst, and the mass ratio thereof is 116-169:116-152:5-15:2-4; the colloidal material comprises nanoparticle A, fluorosilicone oil, silicone oil, solvent A and auxiliary agent A, and the mass ratio thereof is 22-33:40-50:10-20:40-60:4-6; the nano-split solvent comprises nanoparticle B, auxiliary agent B and composite solvent, and the mass ratio thereof is 12-24:4-8:100-120; the nanoparticle A is one or more of nano-silicon dioxide, nano-aluminum hydroxide and nano-titanium dioxide; the nanoparticle B is one or more of gas-phase nano-silicon dioxide and nano-titanium dioxide.

2. The super hydrophobic anti-icing coating based on fluorosilicone rubber according to claim 1, characterized in that: The nanoparticles A are hydrophobically modified by using hexamethylsilazane, perfluorodecyltrimethoxysiloxane or polydimethylsiloxane.

3. The super hydrophobic anti-icing coating based on fluorosilicone rubber according to claim 1, characterized in that: The fluorosilicone oil is one or more of hydroxyfluorosilicone oil with a molecular weight of 67,500 to 82,500, hydroxyfluorosilicone oil with a molecular weight of 58,500 to 71,500, and hydroxyfluorosilicone oil with a molecular weight of 45,000 to 55,000; the silicone oil is one or more of hydroxy silicone oil with a molecular weight of 36,000 to 44,000, hydroxy silicone oil with a molecular weight of 22,500 to 27,500, and hydroxy silicone oil with a molecular weight of 18,000 to 22,000.

4. The super hydrophobic anti-icing coating based on fluorosilicone rubber according to claim 1, characterized in that: The solvent A is one or more of ethyl acetate, butyl acetate and cyclohexanone.

5. The super hydrophobic anti-icing coating based on fluorosilicone rubber according to claim 1, characterized in that: The auxiliary agent A is one or more of tetramethylsilane, KH-550 coupling agent, KH-560 coupling agent, and BYK-012 defoaming agent.

6. The super hydrophobic anti-icing coating based on fluorosilicone rubber according to claim 1, characterized in that: The nanoparticles B are hydrophobically modified by using one or more of polydimethylsiloxane, polydimethyldichlorosilane and hexamethylsilazane.

7. The super hydrophobic anti-icing coating based on fluorosilicone rubber according to claim 1, characterized in that: The auxiliary agent B is one or more of hexamethylsiloxane, perfluorooctyl triethoxysiloxane, and KH-570 coupling agent.

8. The super-hydrophobic anti-icing coating based on fluorosilicone rubber according to claim 1, characterized in that: The composite solvent is one or more of ethanol, isopropanol, propanol and tetrahydrofuran.

9. The super hydrophobic anti-icing coating based on fluorosilicone rubber according to claim 1, characterized in that: The curing agent is one or more of methyl tributylacetonato silane, vinyl tributylacetonato silane and methyl triacetone oxime silane; the catalyst is one or more of dibutyltin dilaurate and stannous octoate.

10. The method for preparing a super-hydrophobic anti-icing coating based on fluorosilicone rubber according to any one of claims 1 to 9, characterized in that: The steps include: Step (1): Nanoparticles A are dispersed in a mixture of deionized water and ethanol for hydrophobic modification; Step (2): dispersing and drying to obtain modified nanoparticles A, preliminarily mixing with fluorosilicone oil and silicone oil, kneading in a vacuum kneader, dispersing, and grinding to obtain a base rubber; Step (3): mixing, dispersing and stirring the base glue, solvent A and additive A to obtain a colloidal material; Step (4): dispersing the nanoparticles B by mixing deionized water and ethanol for hydrophobic modification; Step (5): dispersing and drying to obtain modified nanoparticles B, and uniformly dispersing the modified nanoparticles B with the auxiliary agent B and the composite solvent to obtain a nanoparticle solvent; Step (6): Dispersing the colloidal material, nanoparticle solvent, curing agent, and catalyst, and evacuating the mixture to obtain a finished coating.

Citation Information

Patent Citations

  • High-durability super-hydrophobic self-cleaning coating material and preparation method thereof

    CN101962514A

  • High-strength fluorinated silicone rubber coating and preparation method thereof

    CN115109512A

  • Anti-icing coating and preparation method thereof

    WO2018223781A1